Assessment of the anti-CD40 antibody iscalimab in patients with primary Sjögren's syndrome: a multicentre, randomised, double-blind, placebo-controlled, proof-of-concept study. (March 2020) - Fisher, Benjamin A; Szanto, Antonia; Ng, Wan-Fai; Bombardieri, Michele; Posch, Maximilian G; Papas, Athena S; Farag, Arwa M; Daikeler, Thomas; Bannert, Bettina; Kyburz, Diego; Kivitz, Alan J; Carsons, Steven E; et al.
Summary: Background: Primary Sjögren's syndrome is an autoimmune disease that presents as dryness of the mouth and eyes due to impairment of the exocrine glands. To our knowledge, no systemic therapies for primary Sjögren's syndrome have shown efficacy. CD40–CD154-mediated T cell–B cell interactions in primary Sjögren's syndrome contribute to aberrant lymphocyte activation in inflamed tissue, leading to sialadenitis and other tissue injury. Therefore, we investigated the safety and preliminary efficacy of iscalimab (CFZ533), a novel anti-CD40 monoclonal antibody, in patients with primary Sjögren's syndrome. Methods: This multicentre, randomised, double-blind, placebo-controlled, proof-of-concept study took place at ten investigational sites across Europe (UK, n=4; Germany, Switzerland, and Hungary, n=1 each) and the USA (n=3). Eligible patients were aged 18–75 years and fulfilled the 2002 American European consensus group diagnostic classification criteria for primary Sjögren's syndrome. In the double-blind phase of the trial, patients were randomly assigned (2:1) via computer-generated unique randomisation numbers to receive subcutaneous iscalimab (3 mg/kg) or placebo at weeks 0, 2, 4, and 8 (cohort 1) or intravenous iscalimab (10 mg/kg) or placebo at weeks 0, 2, 4, and 8 (cohort 2). Randomisation was stratified according to baseline intake of oral corticosteroids. At week 12, patients in both cohorts received open-label iscalimab (same dose and route) for 12 weeks. The primary objectives of the study were to assess the safety, tolerability, and efficacy of multiple doses of iscalimab in the two sequential dose cohorts. Safety and tolerability were assessed by adverse events and efficacy of iscalimab versus placebo was assessed by clinical disease activity, as measured by the change in European League Against Rheumatism Sjögren's syndrome disease activity index (ESSDAI) score after 12 weeks of treatment. Analyses were done on a per-protocol basis. The trial was registered with ClinicalTrials.gov, NCT02291029 . Findings: Between Oct 22, 2014, and June 28, 2016, we assessed 82 patients for eligibility (25 for cohort 1 and 57 for cohort 2). 38 patients were excluded because of ineligibility. In cohort 1, 12 patients were randomly assigned to receive either 3 mg/kg doses of iscalimab (n=8) or placebo (n=4), and in cohort 2, 32 patients were randomly assigned to receive either intravenous 10 mg/kg doses of iscalimab (n=21) or placebo (n=11). Adverse events were similar between iscalimab treatment groups and placebo groups, with adverse events occurring in all patients in cohort 1, and in 52% and 64% of the iscalimab and placebo groups, respectively, in cohort 2. Two serious adverse events were reported (one case of bacterial conjunctivitis in cohort 1 and one case of atrial fibrillation in cohort 2), which were unrelated to treatment with iscalimab. Intravenous treatment with iscalimab resulted in a mean reduction of 5·21 points (95% CI 0·96–9·46; one-sided p=0·0090) in ESSDAI score compared with placebo. There was no signficiant difference in ESSDAI score between subcutaneous iscalimab and placebo. Interpretation: To our knowledge, this is the first randomised, placebo-controlled proof-of-concept study of a new investigational drug for primary Sjögren's syndrome that indicates preliminary efficacy. Our data suggest a role of CD40–CD154 interactions in primary Sjögren's syndrome pathology and the therapeutic potential for CD40 blockade in this disease should be investigated further. Funding: Novartis Pharma.